Clinical correlation of doppler ultrasound in pregnancy induced hypertension with special reference to perinatal outcome - Hem Kanta Sarma; Uma Y; Rupak Bhuyan; Pranabika Mahanta (New Indian Journal of OBGYN)
Objective: To identify early high risk fetuses by changes in doppler flow velocity waveforms. Methodology: This was an observational, cross-sectional study of 90 singleton pregnancies in the third trimester with pregnancy induced hypertension. The results of last doppler ultrasound within one week of delivery were used for analysis. Adverse perinatal outcome was studied in the form of emergency caesarean section for fetal distress, APGAR<7 at 5 mins, NICU admission, neonatal morbidity (asphyxia, meconium aspiration syndrome, sepsis) and perinatal mortality. Sensitivity and specificity of various doppler parameters were calculated after comparing with standard. Result: Cerebroplacental ratio and umbilical artery pulsatility index had the highest sensitivity (100%) and Middle cerebral artery resistance index had the highest specificity (97%) in predicting perinatal outcome. Uterine artery doppler evaluation also gives additional information in predicting perinatal outcome. Conclusion – Amongst various doppler parameters cerebroplacental ratio is the best predictor of adverse perinatal outcome. Combination of various parameters is useful in decision making process mainly to decide the timing of delivery.